Hubungan Jenis Persalinan Dengan Waktu Pengeluaran Kolostrum Pada Ibu Bersalin Kala IV di Kota Yogyakarta Tahun 2016 - Almas Azifah Dina; Sumarah Sumarah; Ana Kurniati (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2017)
Expressing colostrum is influenced by several factors, one of them is the type of maternal childbirth. Natural (vaginal) birth and Caesarean Section (C-Section) lead to psychological changes in women, pain, and are associated with the provision of drugs in the mother that can affect colostrum expression soon after birth. The percentage of deliveries by C-Section in Yogyakarta city is 28.6%, the figure is the highest proportion of cesarean delivery in the province. Coverage of exclusive breastfeeding in Yogyakarta city is the lowest in the province that is equal to 54.9%. The purpose of this research is knowing the relation of childbirth types and colostrums expression time on 4th stage of childbirth mothers in Yogyakarta in 2016. This research was an analytic observational study with a prospective cohort design. The study sample consisted of 35 respondents in the group without risk factors and 35 respondents with risk factors conducted from November, 1 to December 21, 2016. Data were collected by interview and observation. The data were analyzed using Chi-Square. Characteristics of mothers in this study were age, parity, nutritional status, and maternal education. The results of the bivariate analysis showed that SC increases the time for expressing colostrum > 120 minutes with the total number of 1.75 (p = 0.031; 95% CI; 1.028 to 2.981). it can be concluded that C-Section can increase the time of colostrum expression by > 120 min.